Over-Expression of ISAba1-Linked Intrinsic and Exogenously Acquired OXA Type Carbapenem-Hydrolyzing-Class D-ß-Lactamase-Encoding Genes Is Key Mechanism Underlying Carbapenem Resistance in Acinetobacter baumannii - Wong, Marcus Ho-yin; Chan, Bill Kwan-wai; Chan, Edward Wai-chi; Chen, Sheng (Frontiers in Microbiology, 2019)
Acinetobacter baumannii is an important clinical pathogen which often causes fatal infections among seriously-ill patients. Treatment options for managing infections caused by this organism have become limited as a result of emergence of carbapenem resistant strains. In the current study, whole genome sequencing, gene expression studies and enzyme kinetics analyses were performed to investigate the underlying carbapenem resistance mechanisms in fourteen clinical A. baumannii strains isolated from two hospitals, one each in Hong Kong and China. A large majority of the A. baumannii strains (11/14) were found to belong to the International Clone II (IC-II), among which six were ST208. Twelve of these strains were carbapenem resistant and found to either harbor blaOXA-23/ blaOXA-72, or exhibit over-expression of the blaOXA-51 gene upon ISAba1 insertion. Enzymatic assay confirmed that the OXA variants, including those of BlaOXA-51, exhibited strong carbapenem-degrading activities. On the other hand, correlation between reduced production of outer membrane porin CarO / expression Resistance-Nodulation-Division efflux AdeB and phenotypic resistance among the test strains was weak, implying that over-production of Carbapenem-Hydrolysing-Class D-ß-Lactamases, especially those encoded by the intrinsic blaOXA-51 gene and the acquired blaOXA-23 and blaOXA-24 elements, are key mechanisms of carbapenem resistance in A. baumannii. This view is confirmed by testing the effect of NaCl, a known BlaOXA inhibitor, which was found to cause reduction in carbapenem MIC by 2 to 8 folds, suggesting that inhibiting OXA type carbapenemases represents the most effective strategy to control phenotypic carbapenem resistance in A. baumannii.